The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0006-87052009000300019
|View full text |Cite
|
Sign up to set email alerts
|

Características químicas de um Latossolo sob diferentes sistemas de preparo e adubação orgânica

Abstract: O não-revolvimento do solo e a incorporação dos resíduos culturais e fertilizantes alteram a disponibilidade e distribuição dos nutrientes no perfil. O objetivo deste estudo foi avaliar as alterações químicas devido aos sistemas de preparo do solo e à natureza das fontes de fertilizantes. O trabalho foi desenvolvido em Latossolo Vermelho distroférrico, no município de Chapecó (SC), no período de 1998 a 2002. O delineamento experimental utilizado foi de blocos ao acaso com parcelas subdivididas e quatro repetiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
4
10
0
4
Order By: Relevance
“…At the dose of 6.222 Mg ha -1 , Zn contents reached 10.13 mg dm -3 , with increment of 41.75% in relation to the manure dose of 1.037 Mg ha -1 . These results corroborate those reported by Scherer & Nesi (2009) Table 2). The increase in pH in H 2 O is due to the higher amount of poultry manure applied on surface, which is related to greater release of cations and mineralization of soil organic matter by microorganisms, transforming it into organic substances (organic and humic acids), which attract cations, as well as the release of NH 4 + , which can have an initial alkaline effect.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…At the dose of 6.222 Mg ha -1 , Zn contents reached 10.13 mg dm -3 , with increment of 41.75% in relation to the manure dose of 1.037 Mg ha -1 . These results corroborate those reported by Scherer & Nesi (2009) Table 2). The increase in pH in H 2 O is due to the higher amount of poultry manure applied on surface, which is related to greater release of cations and mineralization of soil organic matter by microorganisms, transforming it into organic substances (organic and humic acids), which attract cations, as well as the release of NH 4 + , which can have an initial alkaline effect.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained by Rós et al (2013), Scherer & Nesi (2009) and Andreola et al (2000), with the use of poultry manure. These results corroborate those of Moreti et al (2007), who observed that, in the layer of 0.0-0.1 m, Ca contents were higher when using poultry manure and poultry manure + half of the mineral fertilization, attributing it to the higher content of organic matter in the poultry manure, which promotes lower leaching of cations.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results corroborate those obtained by SCHERER & NESI (2009), which showed that the addition of poultry manure and/or pork increased Cu 2+ and Zn 2+ content in the surface layer (0-20 cm) soil, especially in direct planting system. The authors emphasized the effect of manure in Cu 2+ and Zn 2+ soil contents, regardless of tillage system, restricted to the first 20 cm.…”
Section: +No3supporting
confidence: 91%